2006
DOI: 10.1007/s10695-006-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain and pituitary GnRH levels during ovarian maturation in wild female Japanese flounder

Abstract: To elucidate the role of gonadotropinreleasing hormone (GnRH) in gonadal maturation in wild female Japanese flounder Paralichthys olivaceus, we monitored changes in the levels of seabream GnRH (sbGnRH) in the olfactory bulb, telencephalon, hypothalamus, and pituitary during ovarian development together with changes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
3
8
0
2
Order By: Relevance
“…The functions of FSH and LH in terms of oocyte maturation in the Japanese flounder should be further examined in vitro by using an organ culture technique. In the wild Japanese flounder, the intensity of FSH and LH immunostaining was relatively high toward the end of the spawning period, accompanied by a high level of pituitary sbGnRH and low plasma levels of steroid hormones (Pham et al 2006). Similar results were obtained on reared fish -a high level of FSH and LH immunostaining and a low plasma level of steroid hormones were also observed in the postovulatory fish.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The functions of FSH and LH in terms of oocyte maturation in the Japanese flounder should be further examined in vitro by using an organ culture technique. In the wild Japanese flounder, the intensity of FSH and LH immunostaining was relatively high toward the end of the spawning period, accompanied by a high level of pituitary sbGnRH and low plasma levels of steroid hormones (Pham et al 2006). Similar results were obtained on reared fish -a high level of FSH and LH immunostaining and a low plasma level of steroid hormones were also observed in the postovulatory fish.…”
Section: Discussionsupporting
confidence: 73%
“…The fish were sacrificed and the ovaries used for GSI calculation and for histological analysis. The ovarian development of the wild fish was classified into the previtellogenic (PV), early yolk (EY), late yolk (LY), early spawning (ES), late spawning (LS), and termination (TM) stages as described previously (Pham et al 2006). The plasma steroid hormone concentrations were also measured, as in Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…sbGnRH‐ir fibers in the PPD of the pituitary were closely associated with FSH and LH cells, indicating that both FSH and LH cells are the targets of sbGnRH. Moreover, previous results also showed that sbGnRH levels in the telencephalon, hypothalamus, and pituitary changed during ovarian maturation in this species 36 . Taking all results into consideration, it is possible to conclude that sbGnRH is involved in ovarian maturation in the Japanese flounder via stimulating GTH secretion.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, previous results also showed that sbGnRH levels in the telencephalon, hypothalamus, and pituitary changed during ovarian maturation in this species. 36 Taking all results into consideration, it is possible to conclude that sbGnRH is involved in ovarian maturation in the Japanese flounder via stimulating GTH secretion. Although FSH and LH can be produced under stimulation by sbGnRH in the pituitary, the activity of FSH and LH cells in the pituitary during gonadal development should be examined to clarify the precise role of these hormones in Japanese flounder reproduction.…”
Section: Fisheries Sciencementioning
confidence: 98%